The Islamic Education Curriculum in the Sultanate of Oman: Integrating Diversity - Anke Iman Bouzenita; Mohsin Nasser Al-Salimi (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2020)
Islamic Education is one of the required core courses in governmental and private schools in the Sultanate of Oman. This research paper gives an overview over the governmental curriculum for Islamic education, grades 5 to 7, and in how far it considers diversity in its different features. It looks into the ways and methodology used, as well as the design and topics of learning units, with a focus on the means used to integrate diversity on different levels.